Imagewriting : The Verbal Component in Israeli Art Toward the '90s. - Janco-Dada Museum, Ein-Hod; Rehovot Art Gallery, M. Smilanski Center for Culture, Rehovot; Kfar Saba Municipal Gallery, Rehovot (Ein Hod : Janco-Dada Museum, 1991)
Isaac-Polachek, Nurit ; Shaul, Bauman ; Ben-David, Arnon ; Bar-Lev, Jenifer ; Berest, Dganit ; Arie, Eli Gur ; Geva, Tsibi ; Getter, Tamar ; Garbuz, Yair ; Grubman, Michail ; Gershuni, Moshe ; Dagan, Elisha ; etc.
Imagewriting : The Verbal Component in Israeli Art Toward the '90s, Janco-Dada Museum, Ein-Hod, 7.12.1991 - 7.3.1992 / Rehovot Art Gallery, M. Smilanski Center for Culture, 14.3.1992 - 28.4.1992 / Kfar Saba Municipal Gallery, Rehovot, 7.5.1992 - 16.6.1992
boek